2017
DOI: 10.1097/inf.0000000000001394
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, Leptin and Inflammatory Markers in HIV-associated Metabolic Syndrome in Children and Adolescents

Abstract: The prevalence of MetS was similar to that observed in larger cohorts of HIV-infected patients in our setting. Adipocytokine dysregulation seems to be related to MetS in HIV-infected children. A high percentage of patients showed insulin resistance, which should be strictly monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…The association between an elevated BMI and hypertension persisted in models specifically looking at PLWH on cART, adjusted odds ratio of 1.46 (95% CI: 1.13‐1.87), and also among PLWH not on cART with aOR of 1.47 (95% CI: 1.00‐2.16) in agreement with other studies . Pathophysiologically, it has been posited that both HIV itself and ART can cause lipodystrophy leading to accumulation of central adiposity with deep and intricate causal links with hypertension via adipocytokines called adiponectin and leptin . Plasma concentrations of adiponectin, a potent vasodilator through elaboration of endothelial nitric oxide, has been shown to be significantly lower among PLWH with metabolic syndrome .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The association between an elevated BMI and hypertension persisted in models specifically looking at PLWH on cART, adjusted odds ratio of 1.46 (95% CI: 1.13‐1.87), and also among PLWH not on cART with aOR of 1.47 (95% CI: 1.00‐2.16) in agreement with other studies . Pathophysiologically, it has been posited that both HIV itself and ART can cause lipodystrophy leading to accumulation of central adiposity with deep and intricate causal links with hypertension via adipocytokines called adiponectin and leptin . Plasma concentrations of adiponectin, a potent vasodilator through elaboration of endothelial nitric oxide, has been shown to be significantly lower among PLWH with metabolic syndrome .…”
Section: Discussionsupporting
confidence: 87%
“…Pathophysiologically, it has been posited that both HIV itself and ART can cause lipodystrophy leading to accumulation of central adiposity with deep and intricate causal links with hypertension via adipocytokines called adiponectin and leptin . Plasma concentrations of adiponectin, a potent vasodilator through elaboration of endothelial nitric oxide, has been shown to be significantly lower among PLWH with metabolic syndrome . Furthermore, it has been shown that PLWH on cART have higher circulating levels of leptin, which acting via leptin receptors simultaneously trigger activation of both the renin‐angiotensin‐aldosterone pathway and the sympathetic nervous system …”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiologic mechanisms by which HIV-related dyslipidemias induce hypertension are likely related to the adipocytokines adiponectin and leptin. 77,78,79,80,81 Adiponectin, an adipose tissue-derived cytokine or “adipokine”, acts as a vasodilator by stimulating endothelial nitric oxide, 77,78,80 and thus its deficiency has been shown to be critical in the pathogenesis of obesity-related hypertension in the general population. 77 In the context of HIV infection, decreased plasma levels of adiponectin have similarly been associated with metabolic syndrome.…”
Section: Mechanismsmentioning
confidence: 99%
“…77 In the context of HIV infection, decreased plasma levels of adiponectin have similarly been associated with metabolic syndrome. 78,79 For instance, in a cross-sectional study of 54 HIV-infected children and adolescents, adiponectin levels were significantly lower among those with metabolic syndrome (P=0.004). 78 Similarly, in a case-control study of 285 HIV-infected individuals (226 on ART; 59 ART-naïve) stratified by metabolic syndrome, lower adiponectin levels (P<0.0001) and higher concentrations of ROS (P<0.0001) were observed in the plasma of patients with metabolic syndrome, irrespective of ART status.…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation